Submandibular basal cell adenoma - A rare presentation - Fahad Al Qooz; Mohammad Alanazi; Mohammad S. Al Olaimat; Tasneem Malahmeh; Zaid Rasheed Alzoubi (Elsevier, 2024)
A basal cell adenoma is a rare salivary gland tumor that usually occurs in the parotid gland, upper lip, palate, or sometimes the nasal septum. It rarely involves the submandibular gland. To the best of our knowledge, only 6 cases involving the submandibular gland have been described in the literature. We present a case of a 41-year-old female who presented with right submandibular swelling and was diagnosed as having a basal cell adenoma.